Comparing the effectiveness of McMaster’s functional model and Gottman’s cognitive-systemic model in marital conflicts and emotional divorce of divorce applicants - Naseri, Hasan; Babakhani, Vahideh; Amiri Majd, Mojtaba; Jafari, Alireza (Applied Family Therapy Journal (AFTJ), 2023)
Aim: McMaster’s functional model and Gottman’s cognitive-systemic model in marital conflicts and emotional divorce of divorce applicants. Method: The current research method was a semi-experimental type with a pre-test, post-test and follow-up design. In this research, from the number of 85 couples who referred to the psychodynamic psychological interventions clinic due to marital disputes and divorce requests during the year 2020, according to the conditions of the research and with the available sampling method, 21 couples were selected as the research sample. They were randomly placed in three groups (experimental group 1, experimental group 2 and control group). Then, the first experimental group was trained in the McMaster model (Epstein et al., 1978) during ten sessions, and the second experimental group was trained in Gottman’s systemic approach (Gottman, 2019) during ten sessions. The tools used in this research were Gottman’s Emotional Divorce Scale (Gottman, 2008) and Marital Conflicts Questionnaire (Sanaei, 1996), which was used in three stages: pre-test, post-test and follow-up test (three months). Results: The findings obtained from the two-way analysis of variance test (mixed) showed that both therapeutic approaches used in the research (McMaster and Gottman) reduced emotional divorce (F=1598.03; P>0.001) and the reduction of marital conflicts (F=207.14; P>0.001) in couples, and on the other hand, in measuring the durability of the effect, which was followed up, both approaches showed positive results. In the estimation of Bonferroni’s post hoc test, it was found that there is a significant difference between the two approaches, and this means that the effectiveness of McMaster’s approach in reducing emotional divorce as well as reducing conflicts between couples is higher compared to Gottman’s approach. Conclusion: According to the research findings, counselors and psychologists are suggested to pay attention to McMaster’s functional approach in working with couples requesting divorce.